Subcellular rearrangement of Hsp90-binding immunophilins accompanies neuronal differentiation and neurite outgrowth - Quintá, Héctor Ramiro (2010)
FKBP51 and FKBP52 (FK506-binding protein 51 and 52) are tetratricopeptide repeat-domain immunophilins belonging to the tetratricopeptide-protein•hsp90•hsp70•p23 heterocomplex bound to steroid receptors. Immunophilins are related to receptor folding, subcellular localization, and hormone-dependent transcription. Also, they bind the immunosuppressant macrolide FK506, which shows neuroregenerative and neuroprotective actions by a still unknown mechanism. In this study, we demonstrate that in both, undifferentiated neuroblastoma cells and embryonic hippocampal neurons, the FKBP52•hsp90•p23 heterocomplex concentrates in a perinuclear structure. Upon cell stimulation with FK506, this structure disassembles and this perinuclear area becomes transcriptionally active. The acquisition of a neuronal phenotype is accompanied by increased expression of βIII-tubulin, Map-2, Tau-1, but also hsp90, hsp70, p23, and FKBP52. During the early differentiation steps, the perinuclear heterocomplex redistributes along the cytoplasm and nascent neurites, p23 binds to intermediate filaments and microtubules acquired higher filamentary organization. While FKBP52 moves towards neurites and concentrates in arborization bodies and terminal axons, FKBP51, whose expression remains constant, replaces FKBP52 in the perinuclear structure. Importantly, neurite outgrowth is favored by FKBP52 over-expression or FKBP51 knock-down, and is impaired by FKBP52 knock-down or FKBP51 over-expression, indicating that the balance between these FK506-binding proteins plays a key role during the early mechanism of neuronal differentiation.